PENGARUH BRAND IMAGE DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN PRODUK THE BODY SHOP (STUDI KASUS PELANGGAN THE BODY SHOP KOTA SEMARANG) - Indah Putri Marliani; Apriatni Endang Prihatini (Jurnal Ilmu Administrasi Bisnis, 2018)
Cosmetics as a beauty product is a product that is often purchased and selected by female consumers in particular. Cosmetic product is a unique product because besides this product has the ability to complete the basic needs (especially women) for beauty as well as a means for consumers to clarify their identities in society. One of the most popular cosmetics businesses among the society is The Body Shop brand. But The Body Shop has so far not received satisfactory results in its sales in Indonesia and has been outdone by its emerging competitors. Therefore, the effort to attract consumers to have high loyalty is an important thing for the existence of the company continues to awake. This study aims to determine the effect of brand image and product quality on customer loyalty products The Body Shop in Semarang city. This research is an explanatory research by using questionnaire as its instrument. The population and samples used are The Body Shop customers in Semarang City taken as many as 100 respondents by using purposive sampling method. Based on the results of the analysis can be concluded that Brand Image and product quality influence on customer loyalty, evidenced through simple linear regression test with regression value that is equal to brand image of 0.480 and product quality of 0.491. The data analysis techniques are using correlation test, determination test, simple linear regression test, multiple linear regression test, t test and F test with the help of IBM SPSS (Statistical Product and Service Solutions) program version 23. The influence of brand image and product quality together affects customer loyalty by 39.7%. While the remaining 60.3% influenced by other factors. Based on the results of the research, the author can provide advices to The Body Shop in order to maintain the image of natural products that have been attached to the brand, and continue to improve the quality of its products both in terms of packaging and raw materials used.